Consider the following well-formed formulae:
I. $¬∀x(P(x))$   II. $¬∃x(P(x))$   III. $¬∃x(¬P(x))$   IV. $∃x(¬P(x))$
Which of the above are equivalent?

(A) I and III

(B) I and IV

(C) II and III

(D) II and IV

Solution by Happy Mittal

A formula $∀x(P(x))$ is equivalent to formula $¬∃x(¬P(x))$ i.e. add $¬$ inside and outside, and convert $∀$ to ∃$.
So, $¬∀x(P(x))$ is equivalent to $∃x(¬P(x))$.




blog comments powered by Disqus

Consider the following well-formed formulae:
I. $¬∀x(P(x))$   II. $¬∃x(P(x))$   III. $¬∃x(¬P(x))$   IV. $∃x(¬P(x))$
Which of the above are equivalent?

(A) I and III

(B) I and IV

(C) II and III

(D) II and IV

Solution by Happy Mittal[edit]

A formula $∀x(P(x))$ is equivalent to formula $¬∃x(¬P(x))$ i.e. add $¬$ inside and outside, and convert $∀$ to ∃$.
So, $¬∀x(P(x))$ is equivalent to $∃x(¬P(x))$.




blog comments powered by Disqus